Fixed-dose combination drugs containing vitamins: two-step therapy of pain syndrome - Olga A. Shavlovskaya (LLC "MEDIAFORMAT", 2024)
Simple analgesics, non-steroidal anti-inflammatory drugs (NSAIDs), muscular and epidural blocks are most often prescribed to relieve acute pain. However, the use of a number of drugs is associated with the development of unwanted side effects. Furthermore, in some cases the need for both symptomatic and pathogenetic therapy necessitates the prescription of combination treatment involving drugs that exert metabolic effects. The paper discusses the role of metabolic therapy in patients with pain syndrome exemplified by the drugs containing B vitamins. Emphasis is placed on the two-step therapy of pain syndrome.